The Relationship Between Problematic Internet Use and Family Resilience with Risky Behaviors in High School Students in Sari City - Amin Rostamkalai, Sara; Sadeghi, Jamal; Modares, Ashkan; Bagheri Kabodkola, Maryam; Bavand, Proshat (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to examine the relationship between problematic internet use and family resilience with risky behaviors among second-grade high school students in Sari City.Methods and Materials: The research employed a descriptive correlational design. The statistical population consisted of all 1,670 tenth-grade male students enrolled in public high schools in Sari City during the 2022–2023 academic year. Based on the Krejcie and Morgan table and through overestimation, a sample of 325 students was selected using a two-stage cluster sampling method. Data were collected using three questionnaires: the Risky Behaviors Tendency Questionnaire developed by Zadeh Mohammadi and Ahmadabadi (2008), the Problematic Internet Use Questionnaire by Thatcher (2005), and the Family Resilience Questionnaire by Sixbey (2005). Data were analyzed using Pearson correlation and stepwise regression methods.Findings: The findings indicated that there is a significant negative correlation at the 0.01 level between family resilience and students’ risky behaviors. Furthermore, a significant positive correlation at the 0.01 level was found between problematic internet use and students’ risky behaviors. Both family resilience and problematic internet use significantly predicted students’ risky behaviors.Conclusion: These results offer practical implications for psychologists and counselors in improving risky behaviors by considering the impact of family resilience and problematic internet use.